Faktor-Faktor yang Mempengaruhi Pendapatan Petani Durian Montong di Kecamatan Pamona Tenggara - Bimba, Ruth; Taariwuan, Silvany Annatje; Sangkide, Marthen (Interdisciplinary Journal (IDe), 2024)
This study aims to identify the factors influencing the income of Montong durian farmers in Pamona Tenggara District. The research was conducted in several villages within the district using a quantitative approach. Data collection was carried out through a survey using questionnaires distributed to 34 Montong durian farmers. The sample was selected using purposive sampling. The data analysis technique employed was multiple linear regression to examine the influence of independent variables—namely farmer’s age, farming experience, land area, amount of fertilizer, and production volume—on farmer income. The results indicate that, partially, production volume has a significant impact on farmers' income, while other variables such as age, farming experience, land area, and fertilizer amount do not have a significant effect. However, simultaneously, all independent variables collectively have a significant influence on farmers' income. This study provides insights that increasing production volume is the key factor in improving the income of Montong durian farmers